Education and Example: Implementation of Christian Education in Family in Era Society 5.0 - Rezeki Putra Gulo; Restu Gulo (International Journal of Integrative Sciences, 2023)
This article uses a qualitative method. This research discusses the implementation of Christian religious education in families in the era of society 5.0 which is dominated by digital technology. Current advances often create significant problems, such as reliance on social media and a lack of face-to-face interaction between people; Because of excessive and uncontrolled use. This has the potential to damage family harmony and intimacy, including in practicing religious values. This research offers an educational and exemplary approach as a relevant and theological method that parents can use to instill Christian values in families in the era of society 5.0. The education approach refers to direct and directed teaching, while the example approach refers to the attitude of parents setting the right example for their children. The two approaches offered are based on two Bible texts, namely; Titus 2:6-7 and Proverbs 29:17. The narrative of Titus 2:6-7 emphasizes the importance of proper example from parents to children, while the narrative of Proverbs 29:17 emphasizes the importance of proper education from parents to children. The final conclusion of this study is that educational methods and examples are very relevant and accurate when used by parents in implementing Christian religious education in families in the era of society 5.0